2017
DOI: 10.1186/s40168-017-0334-y
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of beneficial bacteria in the skin microbiota of bats persisting with white-nose syndrome

Abstract: Background: Infectious diseases of wildlife are increasing worldwide with implications for conservation and human public health. The microbiota (i.e. microbial community living on or in a host) could influence wildlife disease resistance or tolerance. White-nose syndrome (WNS), caused by the fungus Pseudogymnoascus destructans (Pd), has killed millions of hibernating North American bats since 2007. We characterized the skin microbiota of naïve, pre-WNS little brown bats (Myotis lucifugus) from three WNS-negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(62 citation statements)
references
References 73 publications
0
62
0
Order By: Relevance
“…Our results join a growing body of evidence suggesting that the microbiota can respond to environmental change. Even though we did not detect dysbiosis in these animals, we recognize that dysbiosis of the microbiota may be monitored as an early warning sign about potential downstream effects on host ecology and health (Bahrndorff, Alemu, Alemneh, & Lund Nielsen, 2016;Cheng et al, 2015;Lemieux-Labonté, Simard, Willis, & Lapointe, 2017;Thomason, Mullen, Belden, May, & Hawley, 2017). We further showed that the relative abundances of some core microbiota members are related to innate immune function.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Our results join a growing body of evidence suggesting that the microbiota can respond to environmental change. Even though we did not detect dysbiosis in these animals, we recognize that dysbiosis of the microbiota may be monitored as an early warning sign about potential downstream effects on host ecology and health (Bahrndorff, Alemu, Alemneh, & Lund Nielsen, 2016;Cheng et al, 2015;Lemieux-Labonté, Simard, Willis, & Lapointe, 2017;Thomason, Mullen, Belden, May, & Hawley, 2017). We further showed that the relative abundances of some core microbiota members are related to innate immune function.…”
Section: Discussionmentioning
confidence: 67%
“…dysbiosis of the microbiota may be monitored as an early warning sign about potential downstream effects on host ecology and health(Bahrndorff, Alemu, Alemneh, & Lund Nielsen, 2016;Cheng et al, 2015;Lemieux-Labonté, Simard, Willis, & Lapointe, 2017;Thomason, Mullen, Belden, May, & Hawley, 2017). dysbiosis of the microbiota may be monitored as an early warning sign about potential downstream effects on host ecology and health(Bahrndorff, Alemu, Alemneh, & Lund Nielsen, 2016;Cheng et al, 2015;Lemieux-Labonté, Simard, Willis, & Lapointe, 2017;Thomason, Mullen, Belden, May, & Hawley, 2017).…”
mentioning
confidence: 99%
“…Principal coordinate analysis (PCoA) was performed to get principal coordinates and visualize from complex, multidimensional data. Observed species, Shannon, Simpson, Chao1, and ACE are used to evaluate the complexity of species diversity . OTUs were further used for genome prediction of microbial communities by PICRUSt (Phylogenetic Investigation of Communities by Reconstruction of Unobserved States) …”
Section: Methodsmentioning
confidence: 99%
“…Principal coordinates analysis (PCoA) was performed to get principal coordinates and visualize from complex, multidimensional data. Observed-species, Shannon, Simpson, Chao1, and ACE are used to evaluate the complexity of species diversity (54). Operational taxonomic units (OTUs) were further used for genome prediction of microbial communities by Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) (55).…”
Section: Gut Microbiota Analysismentioning
confidence: 99%